RECONSTRUCTION OF HYPOPHARYNX AND CERVICAL ESOPHAGUS USING A FREE JEJUNAL GRAFT - NEGISHI, TATSUROO; HENTONA, HITOSHI; MURAOK, HIDEKI; NISHIJIMA, WATARU; USUI, HIROYUKI; TAKOODA, SHOJI; MAEDA, SOOKEI; IKEDA, ATSUKO (Nippon Jibi Inkoka Gakkai Kaiho, 1991)
Forty-four patients with cancer in the hypopharynx and cervical esophagus underwent pharyngoesophageal reconstruction with a free jejunal graft after total removal of a tumor combined with resection of the cirumferential tissues. The graft survival rate was 93.2% (41 of 44). Postoperative complications occurred in 16 patients (36.4%), which included postoperative death in one (2.3%), graft necrosis in 3 (6.8%), fistula formation in 4 (9.1%) and graft stricture in 3 (6.8%). All 3 cases of graft necrosis underwent successfully reimplantation. The mean interval time was 20.9 days until oral intake was possible. Thirty-two of 42 patients (76.2%) were able to take usual food. Esophageal speech was limited in the selected cases by this procedure. A cumulative survial rate of 5 years was 40.6% in this series. This method of reconstruction should be advocated as one of relatively safe and reliable procedures for patients with hypopharyngeal and cervical esophageal cancer.